Why medicine needs the church: Reflections on Christianity and medicine in South Africa - Richardson, R. Neville (Koers, 1991)
There is an age-old bond between religion and medicine in which Christianity shares. While it may seem to many that modem medicine has outgrown that bond, Stephen Toulmin observes that medicine has recently rediscovered its need for ethical reflection and Stanley Hauer was argues for the central place of medical care in Christian theology and communal life. In South Africa medicine played an important part in the establishment and development of missions, but the place and role of medical mission work has changed. Far from allowing its medical work to fade, the church in South Africa now needs to see that work in a new light, especially in view of the enormous medical needs of the country. A prerequisite to the addressing of those needs is for the church to rediscover itself as a caring community.